Hubungan Antara Religiusitas dan Dukungan Sosial dengan Kebahagiaan Pelaku Konversi Agama - Pontoh, Zaenab; Farid, M. (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2015)
The purpose of this study was to investigate the relationship between religiosity and social support with happiness among perpetrators of religious conversion. The data was collected from 60 participants who had experienced with religious conversion (muallaf) in Chinese Community. The participants were between 40 and 55 years of age. Data of this study was analysed by using a multiple regression analysisThe results of multiple regression analysis showed F = 20,060 with p = 0, 00 (p < 0, 01), it was revealed that religiosity and social support were found to be highly significant with happiness. Therefore, the result of this study indicated that hypothesis that there is any relationship between religiosity and social support with happiness was accepted. The results of partial correlation analysis were; (1) there was positive correlation between religiosity and happiness (r partial = 0,473, t = 4,056, with p = 0,000 (p<0,01)). It means,by increasing the religiosity, the happiness among perpetrators of religious conversion also will increase and (2) there was no any correlation between social support and happiness among perpetrators of religious conversion(r partial = 0,221 t = 1,715,with p = . 0,092 (p>0, 05)).